Ongoing projects of Turkish Vasculitis Study Group (TRVaS): an update - Firlatan Yazgan, Busra; Ayan, Gizem; Bolek, Ertugrul Cagri; Karadag, Omer (Acta Medica, 2025)
The Hacettepe University Vasculitis Research Centre (HUVAC) initiated prospective patient registration in 2014 to advance clinical and translational research in vasculitis. The transition to a web-based platform enabled the establishment of the Turkey Vasculitis Study Group (TRVaS), which was formally launched in 2021. By 2025, TRVaS had expanded from its initial six centers to a nationwide network comprising 46 centers—14 pediatric and 32 adult rheumatology clinics. Since its inception, TRVaS has developed structured, disease-specific registries and initiated multiple multicenter projects at both national and international levels. TRVaS continues to strengthen Türkiye’s vasculitis research capacity by fostering data collection, promoting large-scale collaboration, and enabling high-quality clinical and translational studies that contribute to global scientific efforts.